Complex multiblock bottle-brush architectures by RAFT polymerization. Issue 87 (18th October 2017) - Kerr, Andrew; Hartlieb, Matthias; Sanchis, Joaquin; Smith, Timothy; Perrier, Sébastien
Abstract : The combination of the reversible addition fragmentation chain transfer (RAFT) polymerization R-group grafting from approach and RAFT one-pot acrylamide multiblock methodology is used to synthesise complex bottle-brush architectures. Abstract : The combination of the reversible addition fragmentation chain transfer (RAFT) polymerization R-group grafting from approach and RAFT one-pot acrylamide multiblock methodology is used to synthesise complex bottle-brush architectures. This is demonstrated for block copolymer grafted side chains and the insertion of ungrafted blocks into the backbone to yield multi-segmented bottle-brushes.